Hew Locke - What have we here? - Locke, Hew 1959-; Seligman, Isabel ca. 20. Jh; Khanna, Indra (The British Museum, 2024)
The accompanying book to the major British Museum exhibition Hew Locke: what have we here? Hew Locke is interested in dissecting the messy and complex ways in which museums are implicated in the histories of empire. ‘This project has enabled me to engage with the Museum’s collection in a much deeper way than ever before, and in a way few artists have had the privilege of doing. I have always been interested in the way objects are interpreted through displays in museums. What story has been distilled and is being told or implied about the past? How does it relate to the present? How can this telling be questioned, disrupted, or complicated?’ The British Museum’s history and collections are closely linked to those of the British Empire, which this book addresses alongside a consideration of today’s often contentious and deeply felt debates around cultural heritage. Focusing on Britain’s historic interactions with Africa, India, and the Caribbean from around 1600 onwards, all of which had an impact on Guyana (where Locke grew up), Locke creates a personal exploration of the subject, weaving in his own words such as the Souvenir series and a new commission titled The Watchers. Using interventionist techniques to reframe the collection’s historical objects, the artist hopes to leave readers with more questions than answers. This book includes a work specifically commissioned for the British Museum which has never been previously published or displayed
Rückseite Titelblatt: Published to accompany the exhibition 'Hew Locke: what have we here?' at the British Museum from 17 October 2024 to 9 February 2025
Includes bibliographical references and index
Keywords: Locke, Hew -- 1959-; Sammlung -- Motiv; Objektkunst; Kultur; Kolonialismus; Kunst; Kolonie; Großbritannien; Locke, Hew / 1959- / Exhibitions; Imperialism / Art; Ausstellungskatalog -- British Museum -- 17.10.2024-09.02.2025 -- London